Konsep Ijtihad dalam Aliran Syiah: Membedah Perdebatan antara Madzhab Ushuliyah dan Akhbariyah - Dwi Aprilianto; Ahmad Suyuthi (Universitas Islam Lamongan, 2021)
This article discusses the division and crisis of Shia religion, one of which was due to the existence of a prolonged khilafiyah within the Shi'a, between the two major groups, Akhbari and Usuli. Akhbari is referred to as a textualist and scripturalist group that rejects rational principles in understanding the texts of the al-Qur’an and Sunnah, while Usuli is a group that accommodates rational principles in understanding texts and concludes ijtihad-based laws. But for those who do not have the qualifications ijtihad is obliged to follow the mujtahid who are known as marja'al-taqlid.